If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+3=4x-33
We simplify the equation to the form, which is simple to understand
x+3=4x-33
We move all terms containing x to the left and all other terms to the right.
+1x-4x=-33-3
We simplify left and right side of the equation.
-3x=-36
We divide both sides of the equation by -3 to get x.
x=12
| 8x+8+5=-19 | | -6x^2=-7x-8 | | 2d+7=d-7 | | 0.055(x+4000)=0.08+0.04(2000) | | 4a^2-52a+144=0 | | 5+6x=x+65 | | 5x+41-6x=1-7x+4 | | 56.08+57.98= | | 96=+4(6x-6) | | 2-5r+2r^2=0 | | 2x^2+6+2x=0 | | 32c+3=15+26c | | 10y-7y-7=47.57 | | 0.6x-0.3(3)=4.5 | | X^3-2x^2-19x+20=5 | | U+7=11 | | q^2+2q=-1 | | 3x^2+49+77=0 | | 8(w-7)=5w-29 | | 3x-5(3-x)=7x+21-5+x | | 5x+6=4(x-2) | | 7(e-8)=98 | | 3(x+7)+6(2x+3)=69 | | 4v-2=5v-6 | | 3x-7x=37 | | 2y-12=12-2p | | 2u=12 | | 2x^4+16x^3+32x^3=0 | | x^2-8x-14=0 | | x^3+8x+14=0 | | (w+3)7=-7 | | 0=x^2-14x+49 |